Portrait of trauma care in Quebec's rural emergency departments and identification of priority intervention needs to improve the quality of care: a study protocol - Fleet, Richard (BMJ Open, 2016)
INTRODUCTION: Trauma remains the primary cause of death in individuals under 40 years of age in Canada. In Quebec, the Trauma Care Continuum (TCC) has been demonstrated to be effective in decreasing the mortality rate among trauma victims. Although rural citizens are at greater risk for trauma and trauma death, no empirical data concerning the effectiveness of the TCC for the rural population in Quebec are available. The emergency departments (EDs) are important safety nets for rural citizens. However, our data indicate that access to diagnostic support services, such as intensive care units and CT is limited in rural areas. The objectives are to (1) draw a portrait of trauma services in rural EDs; (2) explore geographical variations in trauma care in Quebec; (3) identify adaptable factors that could reduce variation; and (4) establish consensus solutions for improving the quality of care. METHODS AND ANALYSIS: The study will take place from November 2015 to November 2018. A mixed methodology (qualitative and quantitative) will be used. We will include data (2009–2013) from all trauma victims treated in the 26 rural EDs and tertiary/secondary care centres in Quebec. To meet objectives 1 and 2, data will be gathered from the Ministry's Database of the Quebec Trauma Registry Information System. For objectives 3 and 4, the project will use the Delphi method to develop consensus solutions for improving the quality of trauma care in rural areas. Data will be analysed using a Poisson regression to compare mortality rate during hospital stay or death on ED arrival (objectives 1 and 2). Average scores and 95% CI will be calculated for the Delphi questionnaire (objectives 3 and 4). ETHICS AND DISSEMINATION: This protocol has been approved by CSSS Alphonse-Desjardins research ethics committee (Project MP-HDL-2016-003). The results will be published in peer-reviewed journals.